Sirtuins and Sepsis: Cross Talk between Redox and Epigenetic Pathways - Anugraha Gandhirajan; Sanjoy Roychowdhury; Vidula Vachharajani (MDPI AG, 2021)
Sepsis and septic shock are the leading causes of death among hospitalized patients in the US. The immune response in sepsis transitions from a pro-inflammatory and pro-oxidant hyper-inflammation to an anti-inflammatory and cytoprotective hypo-inflammatory phase. While 1/3rd sepsis-related deaths occur during hyper-, a vast majority of sepsis-mortality occurs during the hypo-inflammation. Hyper-inflammation is cytotoxic for the immune cells and cannot be sustained. As a compensatory mechanism, the immune cells transition from cytotoxic hyper-inflammation to a cytoprotective hypo-inflammation with anti-inflammatory/immunosuppressive phase. However, the hypo-inflammation is associated with an inability to clear invading pathogens, leaving the host susceptible to secondary infections. Thus, the maladaptive immune response leads to a marked departure from homeostasis during sepsis-phases. The transition from hyper- to hypo-inflammation occurs via epigenetic programming. Sirtuins, a highly conserved family of histone deacetylators and guardians of homeostasis, are integral to the epigenetic programming in sepsis. Through their anti-inflammatory and anti-oxidant properties, the sirtuins modulate the immune response in sepsis. We review the role of sirtuins in orchestrating the interplay between the oxidative stress and epigenetic programming during sepsis.